Imagining the Enlightenment: triumph or exploration? The frontispiece of the Encyclopédie and other programmatic images - Fulda, Daniel (Diciottesimo Secolo, 2025)
How can the concept of ‘Enlightenment’ and its achievements be visualised? This question is worth asking both in relation to our present day and with regard to the protagonists of the historical Enlightenment. The article identifies two ideal types of images of the Enlightenment: one triumphant and one exploratory. As contradictory as they may seem, on closer inspection they prove to be closely related, because both stage the ‘power’ of light and in doing so never appear to be entirely free from the perspective of the other type. What both types demonstrate is the Enlightenment self-image that thinkers and artists of the 18th century already cultivated. From the perspective of historical sources, there is no reason to abandon the historiographical term ‘Enlightenment’, as has recently been called for.